Autonomy Without Accountability? The Governance Challenges of Papua’s Special Fiscal Regime - Siahay, Adolf Z. D.; Salle, Agustinus; Sobirov, Bobur; Abdullah, Siti Intan Nurdiana Wong (International Journal of Economics Development Research (IJEDR), 2025)
Papua’s Special Autonomy Fund represents one of the most ambitious asymmetric decentralization initiatives in Southeast Asia. Yet, over 20 years later, the region remains among Indonesia’s most underdeveloped. This paper investigates the governance failures underlying this paradox, including regulatory overlap, elite capture, and weak local fiscal capacity. It reviews recent evaluation studies and government reports to assess how decentralization design flaws and implementation gaps have constrained service delivery. The analysis offers policy recommendations to restructure the autonomy framework toward greater accountability, data-driven planning, and inclusive development.